1993
DOI: 10.1038/bjc.1993.388
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of DNA ploidy and S-phase fraction and their relation to p53 protein, c-erbB-2 protein and HCG in operable muscle-invasive bladder cancer

Abstract: Summary DNA ploidy and S-phase fraction (SPF), determined by flow cytometry were studied in 118 patients with muscle-invasive transitional cell carcinoma (TCC) of the urinary bladder, scheduled for cystectomy after pre-operative radiotherapy (20 Gy/l week) with or without systemic cisplatin-based neo-adjuvant chemotherapy. The correlation between these parameters and immunohistochemically demonstrated p53, c-erbB-2 and HCG was also investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Many previous studies have investigated the role of histological grade and of proliferative activity in bladder cancer. While the results of these studies unanimously suggest that proliferative activity and histological grade increase with tumour stage, there are discordant results with respect to the clinical significance of these parameters12–16. Most authors have observed significant associations between histological grade and clinical outcome17, 18 but some could not find a link between high histological grade and poor prognosis among bladder cancer patients in subgroups of tumours of one stage19–21.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous studies have investigated the role of histological grade and of proliferative activity in bladder cancer. While the results of these studies unanimously suggest that proliferative activity and histological grade increase with tumour stage, there are discordant results with respect to the clinical significance of these parameters12–16. Most authors have observed significant associations between histological grade and clinical outcome17, 18 but some could not find a link between high histological grade and poor prognosis among bladder cancer patients in subgroups of tumours of one stage19–21.…”
Section: Discussionmentioning
confidence: 99%
“…These studies report HER2 expression rates ranging from 2–74% (Table 3). 57–74 This variation in expression between the different studies is in part due to the differences in methodologies used to assess HER2 and variability in the reporting of data. Both overexpression without gene amplification and heterogeneity in HER2 expression are more common in bladder cancer than in breast cancer 57, 63, 67–68, 70.…”
Section: Salvage Therapymentioning
confidence: 99%
“…In addition to its undisputed role in tumorigenesis, p53 also has prognostic value in terms of response to therapy since most triggers of apoptosis induce and may require p53. From a clinical standpoint, mutations in p53 are usually a poor prognostic indication in a variety of tumor types including gastrointestinal, hematopoietic, breast, and genito-urinary cancers (152,(265)(266)(267)(268)(269)(270)(271)(272)(273)(274)(275)(276)(277).…”
Section: Antineoplastic Therapiesmentioning
confidence: 99%